The Effect of Various Thawing Temperatures of Frozen Semen on the Success of Artificial Insemination of Beef Cattle - Ida Arlita Wulandari; Surya Agus Prihatno (Jurnal Sain Veteriner, 2014)
The study about the effect of various thawing temperatures frozen semen on the success of artificial insemination of beef cattle had been conducted in Residency of Sleman Territory of Yogyakarta. The study used 59 heifers and cows that were oestrus (without oestrus stimulation) with body condition score (BCS) of 3 and 1,5-8 years age. They were inseminated using frozen semen of Simmental thawed in temperature of 37°C, 35°C (warm water) and 28-30°C (cold water). Effect of thawing temperatures was evaluated by non returnrate (NR). NR of thawing temperatures of 37°C, 35°C and 28-30°C were 63,16%, 55%, and 45%. Thawing temperature of 37°C increased the non returnrate compared to the thawing temperatures of 35°C and 28-30°C. Statistical analysis by Chi-square showed there were no differences between thawing temperatures of  37°C, 35°C and 28-30°C on the success of artificial insemination